2021
DOI: 10.1007/s10479-021-04006-2
|View full text |Cite
|
Sign up to set email alerts
|

Handling of uncertainty in medical data using machine learning and probability theory techniques: a review of 30 years (1991–2020)

Abstract: Understanding the data and reaching accurate conclusions are of paramount importance in the present era of big data. Machine learning and probability theory methods have been widely used for this purpose in various fields. One critically important yet less explored aspect is capturing and analyzing uncertainties in the data and model. Proper quantification of uncertainty helps to provide valuable information to obtain accurate diagnosis. This paper reviewed related studies conducted in the last 30 years (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 186 publications
0
38
0
Order By: Relevance
“…Nowadays, deep 2D networks are used for various medical applications such as diagnosis of COVID-19 in CT and X-ray [ 46 , 47 ], and autism spectrum disorders from MRI modalities [ 48 ]. First, in 2012, Krizovsky et al [ 49 ] suggested this network to solve image classification problems, and then quickly used similar networks for different tasks such as medical image classification, in an effort to obviate the difficulties of previous networks and solve more intricate problems with better performance.…”
Section: Epileptic Seizures Detection Based On DL Techniquesmentioning
confidence: 99%
“…Nowadays, deep 2D networks are used for various medical applications such as diagnosis of COVID-19 in CT and X-ray [ 46 , 47 ], and autism spectrum disorders from MRI modalities [ 48 ]. First, in 2012, Krizovsky et al [ 49 ] suggested this network to solve image classification problems, and then quickly used similar networks for different tasks such as medical image classification, in an effort to obviate the difficulties of previous networks and solve more intricate problems with better performance.…”
Section: Epileptic Seizures Detection Based On DL Techniquesmentioning
confidence: 99%
“…Predictive uncertainty estimation (or simply referred as uncertainty estimation in this work) for machine learning models has been widely studied in the literature [16].In general, uncertainty sources can be categorized in aleatoric and epistemic. Aleatoric uncertainty refers to the uncertainty inherent in the measurements [17].…”
Section: A Predictive Uncertainty Estimationmentioning
confidence: 99%
“…Data encryption is usually done by chaotic or hyper-chaotic methods [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In some researches, chaotic or hyper-chaotic systems are used to encrypt peripheral data [ 38 , 39 , 40 , 41 , 42 , 43 ]. In recent years, researchers have focused on the encryption of medical data using chaotic methods [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have focused on the encryption of medical data using chaotic methods [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Medical data contains important information about patients [ 41 , 44 , 45 , 46 ]. Therefore, the confidentiality of medical information is essential when sending it through telecommunication channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation